The unfolded protein response in fission yeast modulates stability of select mRNAs to maintain protein homeostasis - Philipp Kimmig; Marcy Diaz; Jiashun Zheng; Christopher C Williams; Alexander Lang; Tomas Aragón; Hao Li; Peter Walter (eLife, 2012)
The unfolded protein response (UPR) monitors the protein folding capacity of the endoplasmic reticulum (ER). In all organisms analyzed to date, the UPR drives transcriptional programs that allow cells to cope with ER stress. The non-conventional splicing of Hac1 (yeasts) and XBP1 (metazoans) mRNA, encoding orthologous UPR transcription activators, is conserved and dependent on Ire1, an ER membrane-resident kinase/endoribonuclease. We found that the fission yeast Schizosaccharomyces pombe lacks both a Hac1/XBP1 ortholog and a UPR-dependent-transcriptional-program. Instead, Ire1 initiates the selective decay of a subset of ER-localized-mRNAs that is required to survive ER stress. We identified Bip1 mRNA, encoding a major ER-chaperone, as the sole mRNA cleaved upon Ire1 activation that escapes decay. Instead, truncation of its 3′ UTR, including loss of its polyA tail, stabilized Bip1 mRNA, resulting in increased Bip1 translation. Thus, S. pombe uses a universally conserved stress-sensing machinery in novel ways to maintain homeostasis in the ER.